2019
DOI: 10.3390/jcm8010090
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus spp. Act Against Helicobacter pylori-induced Inflammation

Abstract: The bacterial species, Helicobacter pylori, is associated with several gastrointestinal diseases, and poses serious health threats owing to its resistance to antibiotics. Lactobacillus spp., on the other hand, possess probiotic activities that have beneficial effects in humans. However, the mechanisms by which Lactobacillus spp. harbor favorable functions and act against H. pylori infection remain to be explored. The aim of this study was to investigate the ability of bacterial strains, Lactobacillus rhamnosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 54 publications
3
58
0
6
Order By: Relevance
“…Previous studies have shown that the increased Bacteroidetes is associated with dysfunction of innate immune system, resulting in host present in a pro-inflammation state [36], while de ciency of Lactobacillus spp. is involved in gut in ammation and bacterial infection [37]. These results suggest that alteration of microbiota during aging can cause a potent pro-in ammatory effect on aggravating intraintestinal in ammation response, and it may explain why intestinal permeability is increased.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that the increased Bacteroidetes is associated with dysfunction of innate immune system, resulting in host present in a pro-inflammation state [36], while de ciency of Lactobacillus spp. is involved in gut in ammation and bacterial infection [37]. These results suggest that alteration of microbiota during aging can cause a potent pro-in ammatory effect on aggravating intraintestinal in ammation response, and it may explain why intestinal permeability is increased.…”
Section: Discussionmentioning
confidence: 79%
“…It is notable that WMT may be used for refractory H. pylori infection (defined as those who have failed the first eradication treatment or with recurrence of H. pylori infection). Chen et al found that Lactobacillus rhamnosus and Lactobacillus acidophilus had effective antimicrobial activity against multidrug-resistant H. pylori by inhibiting H. pylori -induced inflammation and promoting the growth of probiotics [ 31 ]. WMT, which is also a microbial therapy, may affect the colonization of H. pylori by increasing the abundance of the above probiotics and reducing the inflammation caused by refractory H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…As an emerging adjuvant, probiotics have been used to treat a series of gastrointestinal diseases, including H. pylori infection. In vitro experiments demonstrated that various probiotics have the potential to antagonize H. pylori through their metabolites or bacterial cells [61][62][63]. Sun et al found four Lactobacillus strains isolated from fermented foods in northeastern China were able to inhibit the growth of H. pylori [63].…”
Section: Antagonistic Mechanismmentioning
confidence: 99%
“…Probiotics can inhibit pro-inflammatory factor expression, thereby mitigating the inflammatory response. Numerous studies have shown that probiotic strains such as L. acidophilus, L. bulgaricus, and L. rhamnosus can reduce the expression of IL-8 in H. pylori-infected cells [17,61,80]. Yang et al demonstrated that although H. pylori infection causes the overexpression of IL-8, TNF-α and other pro-inflammatory factors in MKN45 cells, pretreatment with high doses of L. acidophilus La5 can silence the Smad7 and NF-κB pathways, thus relieving the inflammatory response [79].…”
Section: Antagonistic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation